6x+3y=6xy or 2x+4y=5xy
Answers
Answered by
117
1st Equation : 6x + 3y = 6xy --------------- (1)
2nd Equation : 2x + 4y = 5xy -------------- (2)
On solving (1) & (2) * 3, we get
6x + 12y = 15xy
6x + 3y = 6xy
-------------------------
9y = 9xy
x = 1.
Substitute x = 1 in (1), we get
6x + 3y = 6xy
6(1) + 3y = 6(1)(y)
6 + 3y = 6y
6 = 6y - 3y
6 = 3y
y = 2.
Therefore x = 1 and y = 2.
Hope this helps!
2nd Equation : 2x + 4y = 5xy -------------- (2)
On solving (1) & (2) * 3, we get
6x + 12y = 15xy
6x + 3y = 6xy
-------------------------
9y = 9xy
x = 1.
Substitute x = 1 in (1), we get
6x + 3y = 6xy
6(1) + 3y = 6(1)(y)
6 + 3y = 6y
6 = 6y - 3y
6 = 3y
y = 2.
Therefore x = 1 and y = 2.
Hope this helps!
Answered by
41
Solution :
Given equations are,
6x+3y=6xy _____(1)
2x+4y=5xy _____(2)
From eq (1) and (2) ×3
We get,
![\: \: 6x + 3y = 6xy \\ \: \: 6x + 12y = 15xy \\ - \: \: \: \: - \: \: \: \: \: \: \: \: \: \: - \\ - - - - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: 9y = 9xy \\ \: \: 6x + 3y = 6xy \\ \: \: 6x + 12y = 15xy \\ - \: \: \: \: - \: \: \: \: \: \: \: \: \: \: - \\ - - - - - - - - - - \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: 9y = 9xy \\](https://tex.z-dn.net/?f=+%5C%3A++%5C%3A+6x+%2B+3y+%3D+6xy+%5C%5C+%5C%3A++%5C%3A++6x+%2B+12y+%3D+15xy+%5C%5C++-++%5C%3A++%5C%3A++%5C%3A+++%5C%3A+++-++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++++-++%5C%5C++-++-++-++-++-++-++-++-++-++-++%5C%5C++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+9y+%3D+9xy+%5C%5C+)
9y-9xy = 0
9y(1-x) = 0
y(1-x) = 0
=> y = 0 or x = 1
1) If y = 0,
From (i) we get,
6x+3(0) = 6x(0)
6x = 0
=> x = 0
2) If x = 1
From (i) we get,
6(1)+3y = 6(1)y
=> 6 = 6y-3y
=> 3y = 6
=> y = 2
Hence,
x = 0 , y = 0
OR
x = 1 , y = 2
Given equations are,
6x+3y=6xy _____(1)
2x+4y=5xy _____(2)
From eq (1) and (2) ×3
We get,
9y-9xy = 0
9y(1-x) = 0
y(1-x) = 0
=> y = 0 or x = 1
1) If y = 0,
From (i) we get,
6x+3(0) = 6x(0)
6x = 0
=> x = 0
2) If x = 1
From (i) we get,
6(1)+3y = 6(1)y
=> 6 = 6y-3y
=> 3y = 6
=> y = 2
Hence,
x = 0 , y = 0
OR
x = 1 , y = 2
Similar questions